Effectiveness of inoculation with Arbuscular mycorrhizal fungi and Rhizobium sp. on Mimosa caesalpiniifolia seedlings, under different phosphorus levels - Burity, Hélio Almeida; Lyra, Maria do Carmo Catanho Pereira de; Souza, Eidy Simões de; Mergulhão, Adália Cavalcanti do Espirito Santo; Silva, Maria Luiza Ribeiro Bastos da (Pesquisa Agropecuaria Brasileira, 2000)
In order to optimize Mimosa caesalpiniifolia Benth seedlings production, an experiment was carried out to evaluate the inoculation with both arbuscular mycorrhizal fungi (AMF) and Rhizobium. Treatments, arranged in a factorial scheme, consisted of presence or absence of Rhizobium, and of AMF (a mixture of Glomus etunicatum, Acaulospora morrowae and A. longula), with three P levels (equivalent to 0, 20 and 40 kg/ha of P2O5), applied as triple superphosphate. The P application, in the absence or in the presence of AMF inoculation, did not enhance plant development, while the seedlings which received the double inoculation presented significant values on growth, height, leaf area, nitrogenase activity and others analyzed parameters, regardless of the P level. Mimosa caesalpiniifolia nodulation was enhanced by the inoculation with AMF, since plants which received Rhizobium alone showed significantly lower nodulation values than the ones which received both inoculations. There was an increase of the mycorrhizal and a decrease of the esporulation in the presence of Rhizobium.